Women’s awareness of childbirth pain relief methods - Vaitkutė, Akvilė; Gedrimė, Lina (Slauga. Mokslas ir praktika, 2021)
A woman who has acquired knowledge of ways to relieve labor pain has an established attitude about childbirth and accepts it as a physiological process. Training women can increase awareness and improve knowledge about labor pain and ways to alleviate it. The aim of the study – to reveal women’s awareness of ways to alleviate labor pain. Research methods. Analysis of scientific literature; quantitative research; online survey. Results. The results of the study revealed women’s awareness of ways to alleviate labor pain. The results of the study showed that the woman is interested in ways to relieve labor pain. Most subjects are aware of breathing exercises and epidural analgesia, but they also indicated that they would like to learn more about hydrotherapy, choosing the most appropriate posture, massage technique, opioid analgesia, spinal and inhalation analgesics, and the advantages, disadvantages, indications and contraindications of pain relief, efficiency, performance technique and duration of action. Conclusions. Many women use the Internet as their primary source of information on childbirth pain relief. A slightly smaller proportion of women are provided with information by a midwife and a general practice nurse. Such research results show that not all women receive the necessary information from health professionals, so they search for information on the Internet, and such information may not be medically correct and useful for a woman in all cases. Information obtained from websites can scare a woman and the pregnancy becomes tense, childbirth and future pain are taken to wait with fear and anxiety.